A study of the factors affecting the adoption of mobile learning in the workplace - Memeje, Dessa; Talisayon, Serafin (Quezon City University of the Philippines Diliman, 2017)
Mobile learning or mLearning is becoming a new learning method in the workplace among various enterprises, complementing other learning methods such as on-the-job training, stretch projects, coaching, and others. It involves learning applications or solutions delivered through mobile devices such as smartphones and tablets to address users' needs for learning and competency development. The rise of mobile technologies and the growth in the number of the millennial and mobile workforce are further paving the way for mLearning. In most developing countries such as the Philippines, it may be considered to be in its infancy stage, being more prominent in multi-national corporations (MNCs). While it is sill in its early stage, it would be better to understand it further to maximize its potential. The aim of this study is to investigate the driving factors that may affect the adoption of mLearning using the Unified Theory of Acceptance ad Use of Technology (UTAUT) as the conceptual framework. A survey was conducted among 84 Filipino working professionals from both public and private sectors. data were analyzed using statistical software programs. The study found that both performance expectancy and effort expectancy have significant impact on attitude toward using the technology and behavioral intention to use the technology. The findings may be used by the public and private organizations, mobile solutions companies, and others in coming up with strategies, plans, and initiatives to ensure adoption of mobile learning technologies.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Workplace literacy; Education -- Effect of technological innovations on; Mobile learning